Nitrogen Fixing Azotobacter Species as Potential Soil Biological Enhancers for Crop Nutrition and Yield Stability - Aasfar, Abderrahim; Bargaz, Adnane; Yaakoubi, Kaoutar; Hilali, Abderraouf; Bennis, Iman; Zeroual, Youssef; Meftah Kadmiri, Issam (Frontiers in Microbiology, 2021)
Biological nitrogen fixation (BNF) refers to a microbial mediated process based upon an enzymatic “Nitrogenase” conversion of atmospheric nitrogen (N2) into ammonium readily absorbable by roots. N2-fixing microorganisms collectively termed as “diazotrophs” are able to fix biologically N2 in association with plant roots. Specifically, the symbiotic rhizobacteria induce structural and physiological modifications of bacterial cells and plant roots into specialized structures called nodules. Other N2-fixing bacteria are free-living fixers that are highly diverse and globally widespread in cropland. They represent key natural source of nitrogen (N) in natural and agricultural ecosystems lacking symbiotic N fixation (SNF). In this review, the importance of Azotobacter species was highlighted as both important free-living N2-fixing bacteria and potential bacterial biofertilizer with proven efficacy for plant nutrition and biological soil fertility. In addition, we described Azotobacter beneficial plant promoting traits (e.g., nutrient use efficiency, protection against phytopathogens, phytohormone biosynthesis, etc.). We shed light also on the agronomic features of Azotobacter that are likely an effective component of integrated plant nutrition strategy, which contributes positively to sustainable agricultural production. We pointed out Azotobacter based-biofertilizers, which possess unique characteristics such as cyst formation conferring resistance to environmental stresses. Such beneficial traits can be explored profoundly for the utmost aim to research and develop specific formulations based on inoculant Azotobacter cysts. Furthermore, Azotobacter species still need to be wisely exploited in order to address specific agricultural challenges (e.g., nutrient deficiencies, biotic and abiotic constraints) taking into consideration several variables including their biological functions, synergies and multi-trophic interactions, biogeography and abundance distribution.